Mortality in Sahelian goats in Nigeria - Ameh, J.A.; Egwu, G.O.; Tijjani, A.N. (Elsevier, 2000)
The cause of mortality in sahelian goats was investigated in three local government areas of Borno State (Kukawa, Maiduguri and Mongonu) that are known for high goat production. A total of 150 selected flocks (50 flocks from each of the local government areas) were administered questionnaires through spot visits and interviews of the flock owners. On the whole, 644 (21.8%) goats died between May 1996 and April 1997 out of the 2956 goats in the 150 flocks. Mortality (41.4%) was higher in kids (